Monolithic-structured ternary hydroxides as freestanding bifunctional electrocatalysts for overall water splitting. Issue 19 (28th April 2016) - Zhu, Xiaolin; Tang, Cheng; Wang, Hao-Fan; Li, Bo-Quan; Zhang, Qiang; Li, Chunyi; Yang, Chaohe; Wei, Fei
Abstract : Fully exposed ternary hydroxides electrodeposited on Ni foam (NiCoFe/NF) exhibited superb oxygen evolution and hydrogen evolution reactivity in alkaline media, and this monolithic-structured electrode further enabled a high-efficiency water electrolyzer. Abstract : Efficient oxygen and hydrogen evolution electrocatalysts, based on low-cost and earth-abundant elements, are strongly required for sustainable hydrogen production through water splitting. Herein, we fabricated a monolithic-structured electrode by facilely electrodepositing NiCoFe ternary layered double hydroxides (LDHs) onto 3D conductive scaffolds, providing abundant fully exposed active sites for electrochemical reactions. The moderate Co dopant effectively improved the electrical conductivity of the LDH phase and substantially increased its intrinsic activity. When used for oxygen evolution, the as-obtained monolith LDH electrode exhibited superior kinetics with 275 mV overpotential required to achieve 10 mA cm −2 in 0.10 M KOH, as well as a very low activation energy of 21.0 kJ mol −1 . Such a freestanding electrode was also able to catalyze hydrogen evolution efficiently in alkaline media, which further enabled a high-efficiency water electrolyzer delivering 10 mA cm −2 at a very low cell voltage of 1.62 V in 1.0 M KOH. This sheds fresh insight into the principle and process of practical water electrolysis through the rational design of precious-metal-free bifunctional electrodes with a monolithic configuration.